Sight unseen - Kleege, Georgina, 1956- (Yale University Press, 1999)
"This book offers an unexpected and unprecedented account of blindness and sight. Legally blind since the age of eleven, Georgina Kleege draws on her experiences to offer a detailed testimony of visual impairment - both her own view of the world and the world's view of the blind." "Kleege describes the negative social status of the blind, analyzes stereotypes of the blind that have been perpetuated by movies, and discusses how blindness has been portrayed in literature. She vividly conveys the visual experience of someone with severely impaired sight and explains what she can see and what she cannot (and how her inability to achieve eye contact - in a society that prizes that form of connection - has affected her). Finally she tells of the various ways she reads, and the freedom she felt when she stopped concealing her blindness and acquired skills, such as reading braille, as part of a new, blind identity. Without sentimentality or cliches, Kleege offers us the opportunity to imagine life without sight."--Jacket